(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
20th-21st centuries can be distinguished by the development of linguistic and linguocultural directions, characterized by the commonality of some aspects of the research object, interdependence in the field of methodology and terminology. A number of scientists in this research field (Y.D. Apresyan, A.N. Baranov, I.M. Kobozeva, V.V. Petrov and V.N. Pereverzev, Z.D. Popova and I.A. Sternin, R .Shenk, J. Searle and others) is a great service.